De novo CTBP1 variant is associated with decreased mitochondrial respiratory chain activities. (October 2017) - Sommerville, Ewen W.; Alston, Charlotte L.; Pyle, Angela; He, Langping; Falkous, Gavin; Naismith, Karen; Chinnery, Patrick F.; McFarland, Robert; Taylor, Robert W.
Abstract : Objective: To determine the genetic etiology of a young woman presenting an early-onset, progressive neurodegenerative disorder with evidence of decreased mitochondrial complex I and IV activities in skeletal muscle suggestive of a mitochondrial disorder. Methods: A case report including diagnostic workup, whole-exome sequencing of the affected patient, filtering, and prioritization of candidate variants assuming a suspected autosomal recessive mitochondrial disorder and segregation studies. Results: After excluding candidate variants for an autosomal recessive mitochondrial disorder, re-evaluation of rare and novel heterozygous variants identified a recently reported, recurrent pathogenic heterozygous CTBP1 missense change (c.991C>T, p.Arg331Trp), which was confirmed to have arisen de novo. Conclusions: We report the fifth known patient harboring a recurrent pathogenic de novo c.991C>T p.(Arg331Trp) CTBP1 variant, who was initially suspected to have an autosomal recessive mitochondrial disorder. Inheritance of suspected early-onset mitochondrial disease could wrongly be assumed to be autosomal recessive. Hence, this warrants continued re-evaluation of rare and novel heterozygous variants in patients with apparently unsolved suspected mitochondrial disease investigated using next-generation sequencing.